Agapanthaceae, Anthericaceae y Hyacinthaceae (Monocotyledoneae-Asparagales) adventicias en la Argentina - Hurrell, Julio Alberto (2007)
This paper includes updated observations of the previously cited: Agapanthus praecox subsp. orientalis (Agapanthaceae), and 3 new adventitious species for Argentina: Chlorophytum comosum (Thunb.) Jacques (Anthericaceae), Hyacinthus orientalis L. and Hyacinthoides hispanica (Mill.) Rothm. (Hyacinthaceae).